The effect of miR-101 on the memory of rats with a model of Alzheimer’s disease - Berchenko, O. G.; Levicheva, N. O.; Bevzyuk, D. O.; Sokolik, V. V. (Regulatory Mechanisms in Biosystems, 2020)
Memory impairment is a hallmark of Alzheimer’s disease. The clinical diagnosis of the disease is made in the later stages of its development, when specific therapy of the disease is not always effective. Therefore, the detection of early behavioral manifestations of memory disorders in the development of the disease will allow the use of preventive therapy aimed at stopping the death of neurons in brain structures. A neuroethological study of working, spatial, and emotional memory was performed in rats 15–16 months of age with a model of early manifestations of Alzheimer’s disease induced by stereotactic administration of β-amyloid peptide 40 aggregates into the hippocampus. Changes in the neuroethological components of working and spatial memory have been identified. Testing of working memory showed a violation in rats of recognizing the shape of identical objects, reducing experimental activity to unfamiliar objects and their differentiation. Spatial orientation disorders have been identified in the Barnes labyrinth. Emotional memory research has shown the preservation of innate forms of protective adaptive behaviour. At the same time, vegetative indicators reflected an increase in emotional tension. Intranasal administration of liposomal miRNA miR-101 involved in liposomes to rats with a model of early manifestations of Alzheimer’s disease improved neuroethological parameters of working and spatial memory. Restoration of the level of research activity and differentiation of familiar and unfamiliar objects in the testing of working memory in rats has been established. Spatial memory in Barnes labyrinth testing was improved by reproducing spatial orientation skills and relieving emotional stress. Thus, the intranasal use of miR-101 in Alzheimer’s disease is a promising approach to prevent the development of amyloidosis and preserve memory in the early manifestations of Alz-heimer’s disease.